Graphene-Based Hybrid Fillers for Rubber Composites - Jian Wang; Shijiu Li; Li Yang; Baohua Liu; Songzhi Xie; Rui Qi; Yanhu Zhan; Hesheng Xia (Molecules, 2024)
Graphene and its derivatives have been confirmed to be among the best fillers for rubber due to their excellent properties, such as high mechanical strength, improved interface interaction, and strain-induced crystallization capabilities. Graphene rubber materials can be widely used in tires, shoes, high-barrier conductive seals, electromagnetic shielding seals, shock absorbers, etc. In order to reduce the graphene loading and endow more desirable functions to rubber materials, graphene-based hybrid fillers are extensively employed, which can effectively enhance the performance of rubber composites. This review briefly summarizes the recent research on rubber composites with graphene-based hybrid fillers consisting of carbon black, silica, carbon nanotubes, metal oxide, and one-dimensional nanowires. The preparation methods, performance improvements, and applications of different graphene-based hybrid fillers/rubber composites have been investigated. This study also focuses on methods that can ensure the effectiveness of graphene hybrid fillers in reinforcing rubber composites. Furthermore, the enhanced mechanism of graphene- and graphene derivative-based hybrid fillers in rubber composites is investigated to provide a foundation for future studies.